PREVALENCIA, FACTORES DE RIESGO Y MORTALIDAD DE LOS PACIENTES CON CANDIDEMIA ATENDIDOS EN EL HOSPITAL SAN JUAN DE DIOS DURANTE ENERO 2008 A DICIEMBRE 2010 - Zárate Elizondo, Vanessa (2011)
Candidemia is one of most important systemicinfections in hospitalized patients and it is associated with a high risk of mortality. In San Juande Dios Hospital, the last data collected in thismatter, last from 1999. Because of this, a retrospective and descriptive study was made. It wasbased on medical files information, from patientswith a positive blood culture, where Candida sp.was identified. The period of study was betweenJanuary 2008 and December 2010, a 3 yearsperiod.The most frequent species of Candida, the mainrisk factors for this kind of infection, the mortality associated with this disease and the treatmentadministered to the patients were the most im-portant issues assessed.